Visualizing Play: A Case Study of a Camera Phone Game for Playful Re-imaginings of Place. (May 2017) - Hjorth, Larissa
This article explores the unofficial role of camera phone practices in visualizing everyday forms of play as part of emergent urban cartographies. I argue that camera phone practices—especially in an age of timestamping—are creating their own cartographies of place that overlay the visual with the ambient, social with the geographic, emotional with the electronic, in new ways. By focusing upon the playful qualities of camera phone practices, we can begin to understand places as sites for ambient meandering and co-presence. Having outlined the notion of performative cartography as part of what has been defined as "critical cartography, " I consider how camera phone practices can be understood through ambient, co-present play. I turn to a site-specific mobile game, keitai mizu (mobile water), made for a post-Tokyo tsunami and Fukushima disaster context (known as 3/11), to explore the ways in which cartography can be performed.